Unlocking the Potential Morphological Characterization of Sweet Pepper Genotypes - Brahmani, Gandikota; Jindal, S. K.; Patel, S. A. H. (AGRIVITA Journal of Agricultural Science, 2026)
Conserving, cultivating, and categorizing the traditional vegetable varieties is crucial for future food security, as they serve as reservoir of biodiversity. Among that, sweet pepper is an important food crop as it is rich in nutrients. Its demand in India is continuously increasing, highlighting the need to characterize and to evaluate its morphological diversity to improve varietal development programs. Characterizing sweet pepper germplasm can improve breeding programs by selecting parents based on morphological attributes. Forty two genotypes of sweet pepper collected and multiplied from PAU, Ludhiana exhibited the distinct variation for majority of the examined phenotypic traits. Flower morphology with white corolla, pale blue anther along with semi-drooping orientation leads to good fruit set. Square-shaped fruits were predominant and had high consumer preference. Principal component analysis revealed that PC1, PC3, PC8, PC9, PC10, PC14, and PC15 were dominating with fruit attributes Whereas, PC2, PC4, PC6, PC7, PC11, PC12, PC13, and PC16 were pronounced for plant traits and PC5 exhibited dominance for floral attributes. Further cluster analysis revealed that genetic diversity prevailed among the genotypes for morphological attributes aiming the selection of elite parents that can be successfully utilized in the breeding programs as well as conservation of the genotypes for the future.